Entspannung in Europa. Die Bundesrepublik Deutschland und der Warschauer Pakt 1966 bis 1975 - Niedhart, Gottfried 1940- (Zeitgeschichte im Gespräch, 2014)
Gottfried Niedhart analyzes the key role played by West Germany in the process of dètente in Europe, which was understood by the West German political coalitions in power during this period as a means of transcending the status quo. At the same time, he explains the policies of the Warsaw Pact, whose members, unlike West Germany, saw dètente as a means of preserving the status quo